Spatial Variation of Shallow Stress Orientation Along the Hikurangi Subduction Margin: Insights From In‐Situ Borehole Image Logging. Issue 5 (17th May 2022) - Behboudi, E.; McNamara, D. D.; Lokmer, I.; Wallace, L. M.; Saffer, D. M.
Abstract: Knowledge of the contemporary in‐situ stress orientations in the Earth's crust can improve our understanding of active crustal deformation, geodynamic processes, and seismicity in tectonically active regions such as the Hikurangi Subduction Margin (HSM), New Zealand. The HSM subduction interface is characterized by varying slip behavior along strike, which may be a manifestation of combined variations in both stress state and the mechanical properties of faults and their hanging walls. Alternatively, these variations in subduction thrust slip behavior may drive heterogeneity in the stress state in space and time. In this study, we analyze borehole image and oriented four‐arm caliper logs acquired from 13 boreholes along the HSM to present a comprehensive stress orientation data set from borehole data within the shallow (<3 km) upper plate of the subduction thrust. Our results reveal a 065°/245° SHmax orientation within the central HSM (Hawke's Bay region) which rotates to 112°/292° and 140°/320° in the southern HSM. This rotation of SHmax orientation correlates spatially with along‐strike variations in subduction interface slip behavior, characterized by creep and/or shallow episodic slip events in the central HSM and interseismic locking in the south. The borehole SHmax orientations suggest that contemporary stress orientations may be caused in part by along‐strike variation in deformation style imposed by clockwise rotation of forearc. In the southern HSM, borehole‐derived SHmax orientations are inconsistent with SHmax orientations derived from focal mechanism solutions in the subducting plate, implying some degree of mechanical decoupling between the shallow hanging wall and subducting slab. Plain Language Summary: Movement along faults at tectonic plate boundaries is driven by, and in turn can cause changes in the orientation and magnitude of the stresses in the Earth's crust. Such changes may help to explain tectonic forces that cause faulting and build topography, how earthquakes are generated, and the influence of fluids and rock friction on earthquake occurrence. The Hikurangi Subduction Margin (HSM) is New Zealand's largest and most hazardous plate boundary fault, and exhibits a variety of deformation and earthquake types, which may be linked to concomitant variations in stress orientation. In this study, we found that variability in the stress orientations within the upper plate of HSM corresponds broadly to variations in plate boundary slip behavior, and also reflects observed patterns of contemporary surface deformation. We suggest that these shallow stress orientations encode information about subduction plate interface behavior. Key Points: The maximum horizontal stress orientation in the upper 3 km varies along the strike of Hikurangi Subduction Margin Spatial variation of shallow stress orientations is likely related to along‐strike variations in subduction interface coupling behavior Variation of stress orientation along depth in the southern Hikurangi margin may reflect low shear stress on the subduction interface